Method for improving solubility of hemp seed protein by alternating electric field treatment
The alternating electric field treatment technology of hemp seed protein has been modified, which solves the problem of poor solubility, achieves higher solubility and structural looseness, and broadens its application range in food processing.
Patent Information
- Application Number
- CN202411820687.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-18
AI Technical Summary
The poor solubility of hemp seed protein limits its application in food processing.
Alternative electric field (AEF) treatment technology is used to modify hemp seed proteins, and the structural and functional characteristics of the protein are improved by adjusting the electric field strength and reaction time.
AEF-treated hemp seed protein (AEF-HSP) has a smaller particle size, a looser structure, a higher free thiol content and a higher solubility, improving its application potential in food processing.
Smart Images

Figure HDA0005183033820000011 
Figure HDA0005183033820000021 
Figure HDA0005183033820000031
Abstract
Description
Technical Field
[0001] The present invention relates to a method for modifying hemp seed protein and improving the solubility of hemp seed protein with alternating electric field treatment as the core, and pays special attention to the influence of the non-thermal effect generated by the electric field on the structure and functional characteristics of the protein. Background Art
[0002] Hemp seed is a by-product of hemp processing. Hemp seed protein (HSP) extracted after alkali dissolution and acid precipitation is a plant protein that meets the nutritional needs of the human body and has broad research prospects in the food field. HSP is composed of six identical subunits, each of which is mainly composed of an acidic subunit and a basic subunit connected by a disulfide bond. HSP is mainly composed of acidic and basic subunits. The essential amino acids meet the FAO / WHO recommended requirements for infants aged 2-5 years. Compared with soy protein isolate, the proportion of sulfur-containing amino acids and total amino acids is higher, and it has better in vitro enzyme digestibility. About 65% to 80% of HSP is salt-soluble globulin. The high content of sulfur-containing amino acid residues in the HSP structure makes it easy to form intermolecular disulfide bonds, thereby increasing the degree of protein aggregation, which is also one of the reasons why HSP itself has poor solubility. In addition, the excessive presence of β-folds in the secondary structure makes the structure of HSP rigid, which also limits its solubility. However, due to its compact structure, buried hydrophobic groups and intermolecular disulfide bonds, its functional properties are not superior to those of commonly used plant proteins and are usually limited in food processing. Therefore, it is necessary to structurally modify HSP and optimize its specific functional properties to better meet the needs of various food processing.
[0003] Electrical treatment technology is also one of the most widely studied physical processing methods. It has the characteristics of being green, clean, and with low energy loss. Generally, an external electric field is used to treat proteins to change their structure and functional characteristics. It can be divided into pulsed electric field, direct current electric field and alternating electric field (AEF). AEF refers to an electric field with an alternating electric field strength. AEF treatment is similar to pulsed electric field and ohmic heating technology, and is carried out under medium electric field conditions. During the treatment process, the current is alternating current, the electric field strength ranges from 1-1000V / cm, and the frequency is within 1Hz-1 MHz.
[0004] Therefore, AEF treatment was selected as a new electrical treatment method to improve the solubility of HSP, and HSP was treated under the premise of excluding the thermal effect generated by the electric field. The AEF treatment of HSP is to obtain an effective measure for the reuse of hemp processing by-products, thereby broadening the application range of hemp processing by-products. Summary of the invention
[0005] The purpose of the present invention is to address the deficiencies of the prior art and provide a method for treating HSP using AEF treatment as a processing technology. Compared with HSP, the AEF-modified protein (AEF-HSP) has a smaller particle size, a looser structure, an increased degree of exposure of the hydrophobic group, and a higher free thiol content. It also has higher solubility and water contact angle. Focusing on the non-thermal effect of the electrical treatment, it is found that the distribution of the electric field is uniform within a certain range, which is conducive to the modification of HSP by AEF.
[0006] The technical solution adopted by the present invention to solve the above technical problems is: a method for improving the solubility of hemp seed protein by AEF treatment, comprising the following steps:
[0007] (1) Construction of AEF treatment system
[0008] The inner diameter, length, width and height of the quartz reactor are 5.0×5.0×5.0 cm respectively. The electrode plates required for AEF treatment are two titanium electrodes, which are placed at both ends of the quartz reactor and have a thickness of 0.1 cm. In order to ensure the stability of the system, a polytetrafluoroethylene cover is placed above the reactor. The reaction frequency of the entire AEF process is 50 Hz. A sinusoidal AC signal is set using a function generator, and the system is AEF. The signal is amplified by a power amplifier to control the system voltage and electric field strength.
[0009] (2) AEF treatment of hemp seed protein
[0010] HSP was dissolved in a phosphate buffer solution with a pH of 7.4 to prepare a 30 mg / mL HSP solution, which was then transferred to a homemade AEF treatment system. The electric field strength and reaction time in the reactor were adjusted to perform AEF modification of the HSP solution. To ensure uniform modification of the HSP solution, the entire reaction process was carried out under a magnetic stirrer and the system temperature was controlled at 25°C in an ice bath. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 The circular dichroism spectra and secondary structure change diagram of AEF-HSP under different electric field strengths and reaction time conditions; Figure 2 Raman spectra of AEF-HSP under different electric field strengths and reaction times; Figure 3 The fluorescence spectra of AEF-HSP under different electric field strengths and reaction times; Figure 4 Fluorescence microscopy and atomic force microscopy images of AEF-HSPs at AEF treatment conditions of 6 V / cm and 60 min, respectively; Figure 5 Solubility and contact angle of AEF-HSP under different electric field strength and reaction time conditions; Figure 6It is the corresponding relationship diagram of electric field strength-conductivity and electric field strength-energy consumption; Figure 7 Computer simulation of AEF processing. DETAILED DESCRIPTION Specific implementation method one:
[0013] The HSP was treated with a homemade AEF reaction system, and the electric field strength was adjusted to 3, 4, 5, 6, and 7 V / cm. The AEF-HSP was obtained, pre-frozen at -20°C, and then freeze-dried. Specific implementation method 2:
[0015] The HSP was treated with a self-made AEF reaction system, and the reaction time was adjusted to 15, 30, 60, 90, and 120 min. The AEF-HSP was pre-frozen at -20°C and then freeze-dried. Specific implementation method three:
[0017] The effect of AEF treatment on the secondary structure of HSP can be determined by circular dichroism spectroscopy. HSP and AEF-HSP samples were diluted to 0.2 mg / mL with deionized water. The circular dichroism spectroscopy was measured at 25°C, the sample was placed in a 1 mm quartz cuvette, the wavelength range was 190-260 nm, the slit width was 1 nm, the time interval was 0.5 s, and the secondary structure of HSP and AEF-HSP was calculated. Specific implementation method four:
[0019] Raman spectra of HSP and AEF-HSP were measured. The excitation wavelength was 785 nm and the resolution was set to 3 cm -1 , laser power is 80mW, scanning range is 400-2800cm -1 The average spectral data of AEF-HSP is at 1003 cm -1 The phenylalanine band was baseline corrected and normalized, and the Raman spectra of the samples were analyzed using Peakfit v4.12 software. Specific implementation method five:
[0021] The fluorescence spectrum of AEF-HSP samples was measured. An appropriate amount of freeze-dried AEF-HSP powder was dissolved in phosphate to 0.2 mg / mL and measured at excitation wavelengths of 280 nm and 295 nm, respectively, with a scanning range of 300-500 nm. All tests were performed at 25°C. The scanning speed was 600 nm / min, the slit width was 5 nm, and the voltage was set to 600 V. Specific implementation method six:
[0023] (1) The HSP solution before and after AEF treatment was observed under a fluorescence microscope. 25 μL of 1.0 mg / mL Nile blue dye was mixed with 1 mL of 0.02 mg / mL AEF-HSP solution and stained for 30 min. The stained protein solution was dropped onto a glass slide and covered with the slide for microscopic structure observation.
[0024] (2) Atomic force microscopy was performed on the HSP solution before and after AEF treatment. The HSP and AEF-HSP samples were prepared into a 0.2 mg / mL solution, and 0.5 mL of the sample solution was evenly coated on a 1 cm × 1 cm mica sheet and dried at room temperature. The mica sheet was placed on the stage and observed using an AFM microscope. The scanning area covered 1.5 × 1.5 μm, the scanning frequency was 1.0 Hz, and the spring constant was 25.1 N / m. Specific implementation method seven:
[0025] The HSP and AEF-HSP sample solutions were diluted to 0.2 mg / mL and centrifuged at 3000 r / min for 15 min. The supernatant obtained by centrifugation was determined by the Lowry method for protein concentration, and the absorbance at 650 nm was measured by a spectrophotometer. A standard curve was drawn using bovine serum albumin as the standard, and the solubility was calculated as the percentage of supernatant protein content to total protein content. Specific implementation eight:
[0027] The water contact angle of HSP before and after AEF treatment was measured. The freeze-dried sample powder was dissolved in phosphate buffer to prepare a 0.2 mg / mL solution, and 0.5 mL of the sample solution was dropped on a glass slide and air-dried at room temperature. 2.0 μL of deionized water was dropped on a glass slide using a microinjector, and an optical contact angle meter was used to capture the droplet image at a rate of 10 frames per second. Each sample was tested three times, and the water contact angle was calculated using the OCA 20 software according to the Young-Laplace equation. Specific implementation method nine:
[0029] (1) In order to explore the effect of AEF treatment on HSP, the change of conductivity in the HSP reaction system under different electric field intensities was calculated. The calculation formula is as follows:
[0030] σ=IL / AV E=(VIt)
[0031] σ is conductivity, S / m; I is current, A; I is the distance between the two electrodes, m; V is the applied voltage, V; A is the surface area of the electrode, m 2 ; E is energy consumption, J;
[0032] (2) Circular dichroism test:
[0033] In order to quantitatively analyze the secondary structure of proteins, far-ultraviolet circular dichroism spectroscopy can be used for tracking detection, where α-helix has a negative peak at about 222nm, and β-fold has a negative peak at about 208nm. The effect of AEF on HSP and AEF-HSP circular dichroism spectra is shown in Figure 2. Figure 1 shown.
[0034] The main range of changes in the CD spectra of all samples is between 190-260nm, among which the ellipticity peaks at 222 and 208nm are both negative, which is consistent with the characteristics of α-helix and β-fold. With the increase of electric field strength, the θ value of AEF-HSP gradually increases, showing an obvious positive band intensity at 190nm. The intensities of the two negative bands representing α-helix and β-fold decrease at the same time and show a slight red shift, which means that AEF treatment changes the conformation of HSP and the structure of AEF-HSP gradually unfolds. With the extension of reaction time, the negative band intensity of the ellipticity peak at 222 and 208nm wavelengths first decreases and then increases.
[0035] In addition, the change trend of the secondary structure content of AEF-HSP obtained under different conditions is similar to the data change of infrared spectrum fitting. As the electric field strength in AEF increases, the α-helix content of AEF-HSP decreases, which means that under AEF treatment, AEF-HSP gradually unfolds and exposes more reactive sites. The electric field promotes the changes in the arrangement orientation of hydrogen bonds and some electrostatic interactions in the molecules of HSP, thereby affecting the folding state and conformation of the protein.
[0036] (3) Raman spectroscopy test:
[0037] Raman spectroscopy can be used to qualitatively or quantitatively analyze protein secondary structures and changes in protein amino acid residues. -1 The phenylalanine band at the position was normalized, and the characteristic peaks of tyrosine residues, tryptophan residues, and aliphatic amino acid residues in the curve were analyzed. Figure 2 shown.
[0038] The presence of AEF promotes the unfolding of HSP structure, the exposure of tyrosine residues, and the partial disconnection of hydrogen bonds that maintain the tertiary structure. The reason for this phenomenon is related to the interference of current. AEF can interfere with the charge distribution inside the molecule and promote the rearrangement of polar groups. As the reaction time increases, I 850 / I 830 It showed a trend of first increasing and then decreasing, which means that AEF treatment caused the tyrosine residues of HSP to undergo a process of burying-exposure-burying.
[0039] For the tryptophan residues of HSP, a similar trend was shown as for the tyrosine residues. With the increase of the electric field strength, the I760 It shows an upward trend, indicating that the microenvironment around the tryptophan residues changes from buried to exposed. It can be considered that under moderate reaction conditions, the presence of AEF causes the AEF-HSP structure to unfold, which is conducive to the aromatic amino acid residues being exposed to the polar microenvironment as hydrogen bond donors or acceptors.
[0040] 1450cm -1 The characteristic peaks at represent the bending vibrations of -CH, -CH2, and -CH3 of aliphatic amino acid residues. 1450 The intensity of is affected by the hydrophobic interaction between aliphatic amino acid residues. Similar to aromatic amino acid residues, the exposure of aliphatic amino acid residues to the hydrophilic environment is positively correlated with the enhancement of this characteristic peak within a certain range. The effect of AEF on HSP can be discussed in two key factors. As the electric field intensity increases, I 1450 It showed an upward trend, which can be considered that this is related to the AEF treatment promoting the unfolding of protein structure, and the hydrophobic side chain is exposed to the polar environment. 1450 There is also a certain influence, showing a positive correlation within a certain range. When the reaction time is too long, I 1450 The excessive AEF treatment in this state promotes the increase of protein aggregation and gradually enhances the internal hydrophobic effect between hydrocarbons, so that aliphatic amino acids are buried in the hydrophobic environment. This process reflects the dynamic adjustment of the system structure and the change of chemical properties.
[0041] (4) Fluorescence spectrum test:
[0042] In order to explore the effect of AEF on the conformation of HSP, the intrinsic fluorescence spectra of HSP and AEF-HSP were measured. The intrinsic fluorescence spectra of AEF-HSP changed as follows: Figure 3 shown.
[0043] Both the electric field strength and the reaction time affect the tertiary structure of HSP. Compared with the untreated HSP, the presence of AEF increases the fluorescence emission intensity of the AEF-HSP sample, which means that the tertiary structure of HSP is opened, and amino acid residues such as tryptophan and tyrosine buried in the hydrophobic non-polar region of the protein gradually migrate to the hydrophilic region. With the increase of the electric field strength, the fluorescence intensity of AEF-HSP shows a trend of first rising and then falling. The fluorescence intensity reaches the maximum at 6V / cm, and λmax is red-shifted. AEF exposes fluorescent amino acid residues such as tryptophan and tyrosine that were originally hidden inside the protein. The same trend appears in samples with constant electric field strength and gradually extended reaction time in the range of 15-120min. The emergence of this phenomenon may be related to the interference of the current of AEF itself on the electrostatic interaction and hydrophobic interaction within and between HSP molecules. After AEF treatment, the current passes through HSP, and the change of the local electric field has a certain influence on the interaction between amino acid residues, thereby leading to the rearrangement of the internal structure of the protein and structural unfolding.
[0044] (5) Microstructure observation:
[0045] In order to observe the distribution of proteins in aqueous solution, the effect of AEF on the microstructure of HSP was studied. Figure 4 shown.
[0046] All HSP and AEF-HSP samples showed fragmented distribution. The untreated HSP particles were more densely distributed, and there was a local aggregation phenomenon in the distribution of particles. This is because the content of salt-soluble globulin in HSP is high, and the aggregation state between protein molecules in the natural state is mostly maintained by strong intermolecular interactions. AEF treatment promotes the reduction of AEF-HSP particles, and with the increase of electric field intensity and reaction time, it shows a trend of first decreasing and then increasing. At the same time, the particle distribution of AEF-HSP is looser, and the original large pieces of protein are gradually decomposed into smaller particles and evenly dispersed in the aqueous solution. This trend is consistent with the phenomenon presented by the particle size distribution curve. When the electric field intensity is 6V / cm and the reaction time is 60min, it can be considered that AEF-HSP has the best distribution state and particle size. This means that AEF promotes the directional migration of charged particles in protein molecules under the action of electric field force, changes some non-covalent interactions between protein molecules, and thus reduces the size of AEF-HSP particles.
[0047] Under the condition of controlling the thermal effect, the electrical effect of AEF treatment is considered separately, which effectively improves the dispersion state of HSP. In the three-dimensional image of AFM, HSP and AEF-HSP both have evenly distributed peaks, which means that the protein particles are evenly dispersed in the solution. As the degree of AEF treatment deepens, the protein particles may receive more energy input from the electrical effect, causing the originally large pieces of protein to gradually break into smaller particles and evenly disperse in the aqueous solution.
[0048] (6) Solubility determination:
[0049] The treatment of HSP by AEF will affect its solubility. When the electric field strength is between 3-7V / cm and the reaction time is between 15-120min, the solubility changes of HSP and AEF-HSP are as follows: Figure 5 shown.
[0050] The solubility of untreated HSP is the lowest among all samples. This may be related to the structural characteristics of HSP itself. The high globulin and disulfide bond content in HSP makes its interaction with the water environment weak. The solubility of AEF-HSP treated at 3V, 30min and 6V, 15min was improved, indicating that AEF helps to promote the improvement of HSP solubility. This can be explained from the following aspects. First, AEF treatment will increase the molecular flexibility of the protein, promote the local extension of the HSP molecular chain, and cause the protein molecular structure to change from a tight state to a loose state, thereby improving the dispersibility of the sample in the solution. Secondly, the presence of the electric field will also affect the aggregation state of the protein, reduce the formation of protein aggregates, and smaller HSP particles will help improve its solubility. In addition, the non-thermal effect and polar molecular vibration caused by the electric field in the AEF treatment, by affecting the destruction of secondary bonds inside the protein molecules, such as hydrogen bonds, hydrophobic effects, etc., expose the internal groups of HSP and improve its solubility in the solution.
[0051] (7) Contact angle measurement:
[0052] Among the functional properties of proteins, water contact angle is an important parameter to measure the hydrophilicity and hydrophobicity of protein surfaces. The changes in the water contact angles of HSP and AEF-HSP after AEF treatment are shown in Figure 2. Figure 5 shown.
[0053] The water contact angle of untreated HSP is 55.97°, and the water contact angles of all AEF-HSP treated with AEF show varying degrees of increase. The change in contact angle may be related to the change in the molecular structure of the protein. The presence of AEF affects the number of polar and non-polar groups on the surface of HSP and increases its surface hydrophobicity, thereby changing the water contact angle of AEF-HSP. With the increase of the electric field strength, the water contact angle of AEF-HSP shows a trend of first rising and then falling. The reaction time will also lead to similar results. When the electric field strength is 6V / cm and the reaction time is 60min, the water contact angle of AEF-HSP is the largest. The increase in contact angle means that the adsorption capacity of protein at the water-oil interface is enhanced, which helps to reduce the interfacial tension and has a positive effect on the formation of emulsions.
[0054] (8)Conductivity and energy consumption change trends:
[0055] The conductivity of the food matrix will affect the distribution of the electric field and the transmission of current, thus affecting the efficiency and uniformity of the AEF treatment. Figure 6 As shown. In the HSP solution system in the presence of AEF, the conductivity shows a downward trend with the extension of time. When the time is in the range of 0-10min, the conductivity decreases significantly and tends to stabilize at around 20min. When the electric field strength is 3V / cm, the conductivity at the 1st and 30th minutes is observed to be 0.106 and 0.08533S / m, respectively, and the conductivity is reduced to 19.50% of the initial value. From the distribution of the axis-whisker diagram, it can be seen that with the increase of the electric field strength, the conductivity in the HSP solution system shows a downward trend. Comparing the electric field strengths of 3V / cm and 7V / cm, at the 1st, 10th, 20th and 30th minutes of the reaction, the conductivity of the 7V / cm solution system only accounts for 18.81%-19.78% of the 3V / cm system. In addition, the changes in the energy consumption of the AEF-HSP system during the AEF treatment process were also calculated. The changes in energy consumption within 1min, 10min, 20min and 30min under different electric field strength conditions are as follows: Figure 6 Overall, the energy consumption in the AEF-HSP system did not change much during the AEF treatment.
Claims
1. A method for improving the solubility of hemp seed protein by alternating electric field treatment, which is characterized by the following steps: Step 1: The inner diameter, length, width and height of the quartz reactor are 5.0×5.0×5.0cm respectively. The electrode plates required for AEF treatment are two titanium electrodes, which are placed at both ends of the quartz reactor with a thickness of 0.1cm. In order to ensure the stability of the system, a polytetrafluoroethylene cover is placed above the reactor. The reaction frequency of the entire alternating electric field process is 50Hz. A sinusoidal AC signal is set using a function generator, and an alternating electric field is applied to the system. The signal is amplified by a power amplifier to control the system voltage and electric field strength. Step 2: HSP was dissolved in a PBS buffer solution with a pH of 7.4 to prepare a 30 mg / mL HSP solution, and then transferred to a homemade alternating electric field treatment system. The electric field strength and reaction time in the reactor were adjusted to perform AEF modification of the HSP solution. To ensure uniform modification of the HSP solution, the entire reaction process was carried out under a magnetic stirrer and the system temperature was controlled at 25°C in an ice bath. Step 3: Treat HSP with a homemade alternating electric field reaction system, and adjust the electric field strength to 3, 4, 5, 6, and 7 V / cm. Obtain the modified HSP, recorded as AEF-HSP, pre-freeze at -20°C and then freeze-dry. Step 4: Treat HSP with a homemade alternating electric field reaction system, and adjust the reaction time to 15, 30, 60, 90, and 120 min. The obtained AEF-HSP was pre-frozen at -20°C and then freeze-dried.
2. A method for improving the solubility of hemp seed protein by alternating electric field treatment according to claim 1, characterized in that The best alternating electric field treatment conditions were electric field strength of 6V / cm and reaction time of 60min.
3. A method for improving the solubility of hemp seed protein by alternating electric field treatment according to claim 1, characterized in that The solubility of HSP modified by alternating electric field is significantly improved.
4. A method for improving the solubility of hemp seed protein by alternating electric field treatment according to claim 1, characterized in that The water contact angle of HSP modified by alternating electric field is significantly improved.